Design, construction, and magnetic field characterization of a Segmented Adaptive-Gap In-Vacuum Undulator prototype for NSLS-II. Issue 1 (1st December 2022) - Musardo, M.; Chubar, O.; Tanabe, T.; Rank, J.; Banerjee, A.; Corwin, T.; Harder, D.; Eng, C.; Kitegi, C.
Abstract: Segmented Adaptive-Gap in-Vacuum Undulator (SAGU) prototype with different period lengths and gaps in segments for production of high flux and brightness hard X-rays is under development at NSLS-II. According to radiation flux and brightness calculation results, SAGU promises a significant spectral performance gain compared to a conventional in-vacuum undulator, especially in hard X-ray range. In order to reduce the cost of the project, three existing mechanical carriages of Mini-Gap Undulators from the former NSLS X-ray ring were partially de-assembled, redesigned and optimized in order to meet the required mechanical performance of the device. The magnetic module assembly of the first segment has been carried out using a sorting technique which progressively optimizes the magnetic field quality of the device. Additional magnetic tuning, using small dipole kick magnets and virtual shimming, is planned to further improve the electron trajectory straightness, in particular to compensate the angular kicks experienced by the electron beam at segment junctions as it travels through the device. This paper will describe the magnetic and mechanical design as well as the field measurement results, and the magnetic adjustment implemented to properly tune the field strength and minimize the total field integral produced by the segments.